DREPTURILE OMULUI IN CONTEXTUL DIGITALIZARII (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Human Rights in the Context of Digitisation.The purpose of this article is to raise an alarm about the use of digital tools in everyday life. It is not enough to understand the usefulness of digital competence, but we must identify the risks to which we are subject, in such a way as to protect our own fundamental rights but also the rights of those around us. The legal systems of the states have in turn adapted to the new social reality, affected by the evolution of information and communication technologies.But the dynamics of the digital revolution go beyond the legislative process, which makes us have a proactive attitude. Education, correct information on the risks as well as the cooperation of public and private institutions can protect the users of digital tools. We need to strike a balance between access to information and basic human rights. The role of this balance rests with the legislator and the education system.